2021
DOI: 10.52232/ijolida.v3i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Mind Mapping Strategy To Improve Students’ Writing Skills In The EFL Classroom

Abstract: Writing is one of the important language skills to communicate in written forms. Therefore, the improvement of writing skills is absolutely essential to be continually carried out. This study aims at developing writing skills by implementing a mind mapping strategy in the EFL classroom. There two cyclic learning sessions comprising planning, action, observation, and reflection were conducted in this study. The data were collected through administering pre-test, post-test, and questionnaires to the students who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…Teachers in the 21st-century education system must possess many skills to be effective in the contemporary classroom. They need to be proficient in digital literacy, have strong critical thinking and communication skills, be creative and innovative in their teaching methods, be able to collaborate effectively and be adaptable and flexible in their approach to teaching (Handayani & Widiastuti, 2019). By possessing these skills, teachers can create a supportive learning environment for students and help them to develop the skills and knowledge necessary for success in the modern world.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers in the 21st-century education system must possess many skills to be effective in the contemporary classroom. They need to be proficient in digital literacy, have strong critical thinking and communication skills, be creative and innovative in their teaching methods, be able to collaborate effectively and be adaptable and flexible in their approach to teaching (Handayani & Widiastuti, 2019). By possessing these skills, teachers can create a supportive learning environment for students and help them to develop the skills and knowledge necessary for success in the modern world.…”
Section: Introductionmentioning
confidence: 99%
“…As a production process, writing relates to biological aspects that make it meta-performant. Writing conveys messages through graphic symbols, which are arranged logically and systematically in words, sentences, paragraphs, and discourses so that the readers understand their meaning (Mantra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the process of writing, it is necessary not only to write neatly and beautifully, but it also requires precision and creativity. All of this, of course, comes from within the student self (Mantra & Widiastuti, 2019). Thus, to produce writings that contain meaning and can be understood by other people or readers, students must meet a set of writing requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few EFL empirical studies investigated macro skills of reading. Examples of such studies include Mantra, Widiastuti, and Pramawati (2020) that explored micro and macro skills of reading acquired by 40 Indonesian EFL students. The researcher employed ex post facto design for fulfilling the study objectives, and the test results indicated that though the participants' reading comprehension was acceptable at a sufficient level, the students still experienced some challenges related to reading.…”
mentioning
confidence: 99%